Overseas volunteer projects : impacts on development of self among youth volunteers from Singapore. - Nurhamizah Abdul Halim. (2013)
Many researchers have attributed overseas volunteerism as life-changing and generating many positive rewards for volunteers. In recent years, Singapore has observed a rising trend in youths going abroad to engage in volunteering activities. This research paper aims to examine the impacts of overseas volunteer projects on development of self among youth volunteers from Singapore. To achieve that, in-depth qualitative interviews were conducted in order to gain a deeper understanding of volunteers’ motivations in going abroad to volunteer, their volunteering experiences and the impacts that volunteering abroad has had on them. The analysis of data revealed that the impacts of overseas volunteer projects on development of self of volunteers were multi-faceted. Volunteers remarked that as a result of their overseas volunteering experiences, they gained valuable skills and underwent a change in perceptions, developing them into individuals that are more empathetic and confident about themselves and their abilities.